Photo-Fenton interfacial phenomena on graphene oxide: Computational and experimental investigations - Kuntail J.; Verma A.; Kumar S.; Sinha I. (My University, 2025)
For optimum photocatalytic efficiency, besides appropriate band positions, the molecules to be reduced should adsorb on the nucleophilic sites, and those to be oxidized should effectively interact with the electrophilic sites of a photo-excited photocatalyst. The present research investigates the photocatalytic properties of graphene oxide (GO) materials from this novel perspective. We combine density functional theory (DFT) calculations, large-scale classical molecular dynamics (MD), and experimental studies for comprehending the Fenton (in the dark) and visible light photo-Fenton catalytic activities of two GO materials for orange-G (OG) dye degradation. DFT and time-dependent density functional theory (TD-DFT) calculations located a GO model's nucleophilic and electrophilic functionalities in the ground and photo-excited states. Then large-scale classical MD simulations in an aqueous medium gave information about how different reactants interact with varying oxygen functionalities on the GO structure. The photo-Fenton activities of two GO samples with different visible range bandgaps were experimentally evaluated for OG degradation along with these computational studies. The GO photocatalysts efficiently degraded the target dye. Finally, the experimental and computational results are combined to shed light on critical aspects of heterogeneous Fenton and photo-Fenton interfacial phenomena operating on a typical GO structure. © 2021 Elsevier B.V.